Edukasi Ekonomi Biru untuk Komunitas Pesisir: Strategi Peningkatan Nilai Tambah Produk Laut Berbasis Ekonomi Sirkular - Rehatta, Geradin; Wairisal, Paulus Liberthy; Louhenapessy, William George M.; Tuaputty, Hasan (Universitas Pattimura, 2025)
This community service project was conducted in the coastal area of Leitimur Peninsula, Ambon City, to strengthen local economic capacity through the implementation of a blue economy based on circular economic principles. The program aimed to enhance seafood processing skills, promote waste utilization for value-added products, and develop community-based digital marketing. The participatory approach engaged local communities, village authorities, and academics through technical training, entrepreneurship mentoring, and community-based evaluation. The results indicated significant improvement in production capacity, business management, and environmental awareness among coastal residents. This project produced an integrated empowerment model adaptable to local characteristics and replicable in other coastal regions. Recommendations emphasize institutional collaboration to expand sustainable economic impact.